ADVOKASI MAYORITAS MUSLIM TERHADAP MINORITAS HINDU DI SIDOARJO - Fiqil Wiro (LP2M IAIN Palangka Raya, 2021)
This study explored an advocacy of Muslim majority on Hindu Minority in Sidoarjo. The Muslim majority group maintained and protected the Hindu minority group in Krembung community. The Hindu group has very little adherents but they could grow to have a house of worship with a large land area in the East Java region. Most followers came from outside the area. This phenomenon looked unique since the Hindu people living in the temple area are very few and even dominated by immigrants from Bali. There was only one original family and the local indigenous population. The rest were immigrants and followers who came from outside the area. This study attempted to explain the forms of advocacy occurring in the area and factors encouraged the majority to advocate the minority. The analysis method uses advocacy and pro-social theory approaches. To enrich data collection, this study uses field studies which are also accompanied by interviews, observations and documentation. The study revealed that there were some forms of advocacy carried out by Muslim majority on Hindu minority in the form of mutual protection in various fields, including economic, social and the existence of each group. The birth of awareness to build advocacy through various activities was described.